Analysis of unit trusts performance in Singapore. - Tan, Chun Chiah. (2008)
Performance anaylsis of 30 unit trusts in S'pore from period Jun'94 to Jun'99.Three traditional models were used sharpe, treynor, jensen-alpha.Also, 2 advanced models were also applied namely, treynor-mazuy model & bhattacharya-Pfleiderer model.